2013
DOI: 10.11138/mltj/2013.3.2.063
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and musculoskeletal disorders

Abstract: SummaryCigarette smoking has deleterious effects on the musculo-skeletal system. The loss of bone mineral content and increased incidence of fractures are the best known negative consequences. The pathogenesis is complex, due to direct toxic effects on osteoblasts/osteoclasts activity of nicotine, and indirect actions on sex and adrenocortical hormones, vitamin D, intestinal calcium absorption, vessels and oxygen supply. Smoking may favour the onset or aggravate the progression of rheumatoid arthritis and back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 47 publications
(21 reference statements)
5
69
1
6
Order By: Relevance
“…We also collected information on body mass index (BMI) -calculated from height and weight as reported by the patient -and smoking status, which may be correlated with a longer hospitalization as it is associated with medical complications. 19,20 Injury severity characteristics included isolated trauma or polytrauma, upper limb involvement, open or closed fracture, trauma associated with head injury, surgical versus conservative treatment, trauma above or below the knee, time between injury and hospital admission and time between admission and surgery. Socioeconomic status was characterized by employment status (unemployed, employed, retired, autonomous worker, student, other), marital status (married, divorced, single, widower) and patient insurance (none, provincial automobile insurance plan, workers compensation, private insurance).…”
Section: Methodsmentioning
confidence: 99%
“…We also collected information on body mass index (BMI) -calculated from height and weight as reported by the patient -and smoking status, which may be correlated with a longer hospitalization as it is associated with medical complications. 19,20 Injury severity characteristics included isolated trauma or polytrauma, upper limb involvement, open or closed fracture, trauma associated with head injury, surgical versus conservative treatment, trauma above or below the knee, time between injury and hospital admission and time between admission and surgery. Socioeconomic status was characterized by employment status (unemployed, employed, retired, autonomous worker, student, other), marital status (married, divorced, single, widower) and patient insurance (none, provincial automobile insurance plan, workers compensation, private insurance).…”
Section: Methodsmentioning
confidence: 99%
“…It has been also shown that tobacco smoking impacts negatively on the development of diseases of the alimentary tract such as chronic gastric and duodenal ulcer disease, gastroesophageal reflux, Lesniowski-Crohn disease, ulcerating inflammation of the large intestine, intestinal hernia [16,17]. Furthermore, tobacco smoking has been found to influence the development of osteoporosis, parodontopathy, cataract, macular degeneration, early skin aging [18][19][20]. Cigarette smoking has a negative effect on the reproductive system, resulting in small birth weight of the newborn, premature detachment of the placenta or rupture of the membranes, difficulty in becoming pregnant and early menopause [21,22].…”
Section: Cigarette Smoke and E-cigarette Aerosol -Harmfulness To Healthmentioning
confidence: 99%
“…This damage is attributable to alterations in the absorption of vitamin D, high cortisol levels and decreased osteoclast activity; these associated factors reduce bone density, increasing the risk of fractures [43].…”
Section: Physical Therapy In Orthopaedics and Sportsmentioning
confidence: 99%